Rotasi Jabatan Sebagai Mesin Pembelajaran Organisasional: Menguak Dampaknya Terhadap Kompetensi dan Kepuasan Karier Pegawai di Sektor Swasta - Septiani, Sasi; Putri, Synta Aulia; Sabil, Nazwah Nur Sal; Amabhel, Neiva; Surman, Surman (Indo-MathEdu Intellectuals Journal, 2025)
Job rotation is increasingly recognized as an important strategy in building adaptive organizations, yet its effectiveness on improving employee competencies and career satisfaction in the private sector has not been extensively studied. This study aims to analyze the influence of job rotation on employee competence development, both in terms of technical and behavioral competencies. This study uses a qualitative descriptive approach with thematic analysis to reveal how job rotation not only moves employees between functions, but also shapes learning experiences that accelerate professional growth. By integrating Kolb's experiential learning theory (1984), Spencer & Spencer's competency model (1993), and Greenhaus et al.'s career satisfaction framework (2010), this study finds that strategically managed job rotation can accelerate competency development and enhance career satisfaction through motivation, clarity of direction, and cross-functional insights. However, unstructured rotation policies may hinder these benefits. This study provides a new perspective on job rotation as a transformative and sustainable career development tool.